1983
DOI: 10.1021/j100231a034
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the adsorption-desorption of phosphate on the .gamma.-alumina surface using the pressure-jump technique

Abstract: Double relaxations were found in aqueous -1203 suspensions containing mono-and divalent phosphate ions by using the pressure-jump technique with electric conductivity detection. The relaxations were observed over the range of pH 5-8.5, where the major phosphate adsorption site is the protonated surface hydroxyl group. The fast relaxation time decreases with pH, while the slow one increases. Taking into account the surface potential calculated from the ("-potential on the basis of the Davis, James, and Leckie m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 3 publications
3
20
0
Order By: Relevance
“…[55] ) Rates for sites on an oxide surface are not yet directly measurable by using conventional 17 O NMR spectroscopic and mass spectrometric methods. [91][92][93] Unlike the aquo ions, the water molecules bound to surface sites are often structurally isolated from one another.…”
Section: Lifetimes Of Bound Water Moleculesmentioning
confidence: 99%
“…[55] ) Rates for sites on an oxide surface are not yet directly measurable by using conventional 17 O NMR spectroscopic and mass spectrometric methods. [91][92][93] Unlike the aquo ions, the water molecules bound to surface sites are often structurally isolated from one another.…”
Section: Lifetimes Of Bound Water Moleculesmentioning
confidence: 99%
“…Such studies have included the hydrolysis of hydroxyl groups on Zeolite surfaces (Ikeda et al, 1982a), adsorption-desorption kinetics of protons at the Ti0 2 -H 2 0 interface (Ashida et al, 1978), kinetics of 10 3 on Ti0 2 (Hachiya et al, 1980), proton adsorption-desorption mechanisms on Fe oxides (Astumian et al, 1981), adsorption-desorption dynamics of acetic acid on silica-alumina particles (Ikeda et al, 1982b), and NH: adsorption on zeolites (Ikeda et al, 1984). A number of other adsorption and/or desorption kinetic studies, all on Al oxide, have included interactions with Pb (Hachiya et al, 1979;Hayes and Leckie, 1986), phosphate (Mikami et al, 1983a), chromate (Mikami et al, 1983b), and other metals (Hachiya et al, 1984a,b).…”
Section: B Kinetic Approachesmentioning
confidence: 99%
“…Independent spectroscopic evidence has been cited to validate use of inner-sphere surface complexes for phosphate (12), arsenate (15), selenite, and selenate (20) adsorption. Pressure-jump kinetic experiments have been linked with surface complexation modeling to establish adsorption mechanisms for phosphate (17), chromate ( 21 ), lead (6), molybdate (22), sulfate (23), selenite, and selenate (24). However, since results from surface complexation modeling of an equilibrium study are necessary to analyze the kinetic data, this approach is not independent.…”
Section: Introductionmentioning
confidence: 99%
“…However, since results from surface complexation modeling of an equilibrium study are necessary to analyze the kinetic data, this approach is not independent. Mikami et al (17), using pressure-jump kinetics with surface complexation modeling, concluded that phosphate ions adsorb on aluminum oxide as outer-sphere surface complexes. This conclusion directly contradicts much experimental evidence supporting an inner-sphere adsorption mechanism for phosphate (25).…”
Section: Introductionmentioning
confidence: 99%